2009
DOI: 10.1007/s12325-009-0083-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cognitive response to extended-release methylphenidate (Medikinet®) in attention deficit/hyperactivity disorder: Efficacy evaluation

Abstract: Mph-ER improved attention and self-control from a clinical and cognitive point of view. Of those studied, the CPT-II was the most effective neuropsychological test for monitoring efficacy of Mph in the short-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
0
12
0
3
Order By: Relevance
“…[16][17][18][19] CPT tests have a potential role in monitoring the need for ongoing therapy in children with ADHD after a prolonged period of stimulant pharmacotherapy. 20 Few studies have demonstrated the superiority of CPT tests for assessing the effects of psychostimulants in ADHD patients over other laboratory tools for measuring vigilance such as 21 A recent review has presented a balanced view of the usefulness and limitations of CPT tests in monitoring the effects of psychostimulants.…”
Section: Cost Implicationsmentioning
confidence: 99%
“…[16][17][18][19] CPT tests have a potential role in monitoring the need for ongoing therapy in children with ADHD after a prolonged period of stimulant pharmacotherapy. 20 Few studies have demonstrated the superiority of CPT tests for assessing the effects of psychostimulants in ADHD patients over other laboratory tools for measuring vigilance such as 21 A recent review has presented a balanced view of the usefulness and limitations of CPT tests in monitoring the effects of psychostimulants.…”
Section: Cost Implicationsmentioning
confidence: 99%
“…CPT outcome measures are associated with ADHD symptomology: false positive errors (i.e., response to a non-target stimulus) are associated with impulsivity, while true positive errors (i.e., non-response to a target stimulus) are associated with inattention [1921]. ADHD patients make more false positive errors than healthy adults, and these errors are sensitive to the effects of stimulant treatment in ADHD patients [2225]. Furthermore, performance on this task is sensitive to effects of methylphenidate, an efficacious ADHD treatment [2427].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, un 20-25% de niños y adolescentes con TDAH, atendiendo a los criterios actuales, no muestran problemas ejecutivo-atencionales en la psicometría. Desconocemos si estos casos son una fenocopia del TDAH o un subtipo dentro de este trastorno; estos casos, adicionalmente, parecen mostrar una menor respuesta al tratamiento farmacológico y un desarrollo cortical propio de individuos control sin TDAH [29,30]. En la misma línea, podemos observar en la consulta que pacientes con marcados problemas escolares o sociales, que no cumplen criterios clínicos del TDAH, muestran dificultades atencionales marcadas en la evaluación psicométrica; estos casos acaban tipificados dentro de los apartados 'otro TDAH especificado' o 'TDAH no especificado' [1].…”
Section: Declaración De Interesesunclassified